Village Baseline Study: Site Analysis Report for Makueni – Wote, Kenya (KE0202) - Onyango, Leah; Mango, Joash; Loo, L.; Odiwuor, H.; Mwangangi, M.; Mutua, Edna N.; Mutuo, T. (2013)
The village baseline study of Kithoni village in the CCAFS benchmark site of Makueni, Kenya took place from June 11th – 14th, 2012. Focus group discussions were conducted separately for men and women. The village is in a marginal landscape and is food insecure. Frequent droughts and crop failures plague the area. The biggest constraint to agricultural production is the shortage of water. Land holdings have become increasingly smaller due to the increase in human population. The government has to frequently provide relief food during times of crisis. There are many organisations operating in the village, but there is a lack of concerted efforts between them, particularly those working in food security and natural resource management. Very few organisations are working on the food crisis situation in the area, although this is a frequently recurring issue. Networks of information for agricultural advice are based mainly on the radio and friends/neighbours. All the organisations mentioned as providing information are those that operate beyond the locality. There is potential to link these organisations with community groups and individuals especially to develop a feedback mechanism so that the flow of information is two-way. The FM stations can also be supplied with a wider range of information to disseminate. However, this must be in line with the community needs which should be established beforehand.